Розклад випадкових величин у тригонометричні стохастичні ряди - Заболотній, С.В. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The possibility of decomposition of random variables in trigonometrically stochastic series is considered in this work. The coefficients of decomposition are deducted from condition of minimization of main square error of decomposition. The results of simulation of this decomposition are resulted.